Peningkatan Mutu dan Efisiensi Keripik Ubi dengan Teknologi Rendah Minyak di UMKM Bu Inun Bangkinang, Kampar - Putri, Dini Amalia; Kurniaty, Tri; Afifah, Belia; Dewi, Ilma Satriana; Yogy Rasihen; Agung Pramono; Rezki Putra (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
Food-based micro, small, and medium enterprises (MSMEs) play a crucial role in supporting household economic growth, including in Sialang Village, Bangkinang Subdistrict. One of the local businesses, “Keripik Cabe dan Mie Kuning Bu Inun,” produces cassava chips using traditional frying methods, which result in high oil absorption, inconsistent quality, short shelf life, and low production efficiency. Limited knowledge of food processing technology, sanitation, and food safety standards further hinders business development. This community service program aims to address these challenges through the application of low-oil frying technology, training on Good Manufacturing Practices (GMP), production assistance, and periodic evaluation. The implementation method includes field observation, technical training, technology demonstration, production mentoring, and monitoring. The results show significant improvements in product quality, indicated by lower oil content, crispier texture, brighter color, and longer shelf life. Efficiency in oil usage and process stability also increased. Moreover, the knowledge and skills of MSME actors in sanitation, food safety, and production management improved considerably. Overall, the program successfully enhanced the competitiveness of the MSME, strengthened production sustainability, and provided positive economic impacts. This initiative can serve as a replicable model for other food MSMEs facing similar challenges.